Free-flow electrophoresis in the proteomic era: a technique in flux - Islinger, Markus; Eckerskorn, Christoph; Völkl, Alfred (Electrophoresis, 2010)
Since its introduction five decades ago, free-flow electrophoresis (FFE) has been mainly employed for the isolation and fractionation of cells, cell organelles and protein mixtures. In the meantime, the growing interest in the proteome of these bio-particles and biopolymers has shed light on two further facets in the potential of FFE, namely its applicability as an analytical tool and sensor. This review is intended to outline recent innovations, FFE has gained in the proteomic era, and to point out the valuable contributions it has made to the analysis of the proteome of cells, sub-cellular organelles and functional protein networks.
First published: 26 May 2010
Gesehen am 11.07.2023